Isolation of L-Asparaginase from Natural Waste: Squid Cartilage Bone - Batool, Tahira; Makky, Essam A.; M. M., Yusoff (2014)

(untitled)
Rapid industrial development in Malaysia has led to the generation of huge quantities of hazardous wastes, which have aggravated the environmental problems in the country. Rational and right utilization of waste always results in socio-economic development. The current study focus on isolation, identification and screening of microorganisms from natural waste for maximum L-asparaginase production and to minimise the problems caused by waste matter in Malaysia. L-asparaginase (L-asparagine amino hydrolase, E.C.3.5.1.1) is a therapeutically important enzyme used in combination with other drugs in the treatment of acute lymphoblastic leukemia and lymphosarcoma, widely found in biological world and can be produced through microbial fermentation from natural waste (from waste to wealth). It is also used in food industry for the production of acrylamide (a potent carcinogen and a neurotoxic compound) free starchy fry food. In this study, for L-asparaginase production using natural waste (squid cartilage bone) as substrate, thirty one bacterial and four fungal isolates were analysed. Nutrient agar media has been used for bacterial isolates and potato agar media (PDA) for fungal isolates. Inoculum was prepared for both fungal and bacterial isolates. Cell free filterate was obtained after incubation and used as crude enzyme. Nessler’s reaction was used to assay the asparaginase activity using UV-visible spectrophotometer. Two fungal and two bacterial isolates namely, T.reesei, C.albicans , E.coli, and A9, have been chosen for further studies on the basis of higher enzyme productivity.